Metaphors in the Quran and its translation accuracy in Indonesian - Nurbayan, Yayan (Universitas Pendidikan Indonesia, 2019)
Metaphors (majaz in Arabic) are an important part of language style. In the Quran, they play a vital role in different interpretations of the Quran. The use of metaphors in Quranic verses may often cause semantic problems and varied interpretations for translation. The study of metaphors pertaining to the Quran aims to investigate accuracy issues in its translation. Previous studies on the translation of the Quran into Indonesian suggest that some metaphors are translated word-for-word. To some extent, the literal translation is an oxymoron leading to reduced nuances of meaning. The present study seeks to address two issues in relation to the use of metaphors: the actual translation product of Quranic metaphorical verses and translation techniques for Quranic metaphorical verses produced by the Ministry of Religious Affairs. In doing so, this study examines the metaphors of 15 verses in the Quran. Findings show that containing metaphors (13 verses containing lexical metaphors, and 2 verses containing sentential metaphors). Regarding the techniques, in the translated Quran published by the Ministry of Religious Affairs, 13 verses were translated by a literal technique and 2 verses by a non-literal technique. The findings of this suggest that when translating Quran verses, metaphorical features should be taken into account. It is also imperative for future research to scrutinize the implications of different translations on the construction of meaning in the Quran.